Design, preparation and performance of novel three-dimensional hierarchically porous carbon for supercapacitors. (10th August 2015) - Zhao, Qinglan; Wang, Xianyou; Xia, Hui; Liu, Jing; Wang, Hao; Gao, Jiao; Zhang, Youwei; Liu, Jia; Zhou, Heye; Li, Xiaolong; Zhang, Shuyang; Wang, Xingyan
Highlights: Nitrogen-doped three-dimensional hierarchically porous carbon is synthesized under mild condition. The N-3DHPC shows the hierarchical porosity and the surface nitrogen-doping. The high specific capacitance of 308.4 F g −1 is achieved. The energy density of N-3DHPC supercapacitor is still as high as 9 Wh kg −1 even at 5000 W kg −1 . Abstract: A novel nitrogen-doped three-dimensional hierarchically porous carbon (N-3DHPC) has been designed and prepared by the carbonization of polyaniline (PANI) covered on the three-dimensional macroporous carbon (3DMC), followed by KOH activation to generate micropores and mesopores on the wall of macropores. The pore structure, morphology and surface physicochemical properties of the carbon samples are characterized by nitrogen adsorption/desorption isotherm, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and elemental analysis. The N-3DHPC inherits the morphology of the pristine 3DMC and processes a hierarchically porous structure with a high specific area of 1084.0 m 2 g −1 and some nitrogen-doped species on the surface. The electrochemical behaviors of the N-3DHPC are characterized by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) test, electrochemical impedance spectroscopy (EIS) and cycle life measurement. The results show that the N-3DHPC obtains high specific capacitance of 308.4 F g −1 at a current density of 1 A g −1 . Moreover, the N-3DHPC supercapacitor exhibits excellent rate performance, low resistance, high energy density of 10.7 Wh kg −1 at the power density of 500 W kg −1 and excellent cyclic stability with the specific capacitance retention of 96 % even after 10000 cycles, thus the N-3DHPC will be a promising electrode material for supercapacitors.